Prospective Patient-Related Outcome Evaluation of Secondary Cleft Rhinoplasty Using a Validated Questionnaire. (July 2017) - Sawyer, Adam R.; Robinson, Stephen; Cadier, Michael
Objective: To evaluate patient satisfaction and quality of life following secondary cleft rhinoplasty. Design: Prospective consecutive patient, single unit, single surgeon study. Setting: Spires Cleft Centre, Salisbury, Wilshire, United Kingdom, and private practice. Patients, Participants: 56 (27 secondary cleft rhinoplasty) patients completed evaluation forms preoperatively and 3 to 6 months postoperatively. Interventions: Subjective assessment was performed using a validated Rhinoplasty Outcomes Evaluation (ROE) questionnaire. This instrument comprises six questions that capture three quality-of-life domains: physical, mental/emotional, and social. Main Outcome: Rhinoplasty outcomes evaluation scores were calculated (range = 0 to 100) to indication satisfaction with rhinoplasty outcomes. Results: Average age was 28 years (range = 18 to 59 years). There was a significant subjective improvement in the total ROE evaluation scores from 28 ± 10 to 80 ± 11 ( P < .01) in secondary cleft rhinoplasty. Similar results were achieved in noncleft rhinoplasty 34 ± 9 to 84 ± 9 ( P < .01). Specific scores for nasal aesthetic appearance improved from 0.3 ± 0.2 to 3.2 ± 0.3 ( P < .01) in secondary cleft rhinoplasty. No significant change was seen in breathing capacity in secondary cleft rhinoplasty (from 2.7 ± 0.3 to 3.2 ± 0.2; P = .29). All patients said they would undergo the procedure again. Conclusion: Our results demonstrate high patient satisfaction after cleft rhinoplasty with particular regard to cosmetic appearance. These results are similar to those for noncleft rhinoplasty. We would recommend the use of this simple and quick validated outcome tool with all rhinoplasty patients.